The effect of human leukocyte antigen A1 and B35‐Cw4 on sustained BK polyomavirus DNAemia after renal transplantation. Issue 12 (28th October 2020) - Hosseini‐Moghaddam, Seyed M.; Xu, Qingyong; Jevnikar, Anthony M.; House, Andrew A.; Luke, Patrick; Campigotto, Aaron; Kum, Jina J.Y.; Singh, Gagandeep; Alharbi, Hajed; Speechley, Mark R.
Abstract: Human leukocyte antigen (HLA) class I presentation pathway plays a central role in natural killer (NK) cell and cytotoxic T‐cell activities against BK polyomavirus (BKPyV) DNAemia. We determined the risk of sustained BKPyV DNAemia in 175 consecutive renal transplant recipients considering the simultaneous effect of donor/recipient HLA class I antigens and pre‐ or post‐transplant variables. Median (IQR) age was 53 (44‐64) years, and 37% of patients were female. 40 patients (22.9%) developed sustained BKPyV DNAemia [median (IQR) viral load: 9740 (4350‐17 125) copies/ml]. In the Cox proportional hazard analysis, HLA‐A1 (HR: 3.06, 95% CI: 1.51‐6.17) and HLA‐B35‐Cw4 (HR: 4.63, 95% CI: 2.12‐10.14) significantly increased the risk of sustained BKPyV DNAemia, while 2 HLA‐C mismatches provided a marginally protective effect (HR: 0.32, 95% CI: 0.10‐0.98). HLA‐Cw4 is a ligand for NK cell inhibitory receptor, and HLA‐B35 is in strong linkage disequilibrium with the HLA‐Cw4 allele. The association between HLA‐B35‐Cw4 expression and sustained BKPyV DNAemia supports the important role of cytotoxic T cells and NK cells that would normally control BKPyV activation through engagement with immunoglobulin‐like killer receptors (KIRs). Further studies are required to investigate the effect of HLA‐C alleles along with NK cell activity against BKPyV DNAemia.